Psidium cattleyanum Sabine: a influência do conteúdo de DNA na formação de quimiotipos e na atividade em diferentes modelos biológicos - Spadeto, Micheli Sossai (2019)
Polyploidy is defined as the presence of two or more chromosomal assemblies in an organism and has been reported as one of the most important mechanisms of plant speciation and diversification, and may result from the fusion of two genomes of distinct species (alopoliploidia) or genomes of individuals of the same species (autopolyploidy). Gene duplication in polyploid plants generates high inter and intraspecific variability, which may influence the production of secondary metabolites and, consequently, the chemical composition of essential oils and the formation of different chemotypes. Within the genus Psidium (basic chromosome number x = 11), some species have been described as polyploids, among them, Psidium cattleyanum Sabine. For this species, cytogenetic studies reported nine cytotypes, with chromosome numbers ranging from 2n = 22 to 2n = 132 chromosomes. In this context, considering the existence of this variation in ploidy in P. cattleyanum, the present work aimed to study the influence of this variation on the qualitative and quantitative production of different essential oil chemotypes and also to relate the different DNA contents with the biological activity of these oils in Lactuca sativa, Sorghum bicolor and Aedes aegypti. Through flow cytometry it was possible to observe differences in the DNA content of the analyzed plants and by chromatographic profile analysis were also identified three distinct chemotypes. Plants with higher DNA content (6.03 and 5.81pg) showed higher yield and are mostly composed of hydrogenated sesquiterpenes, while plants with lower DNA content (3.95, 3.23, 3.80 and 3.20pg) produce less oil and are composed. by hydrogenated monoterpenes. In addition, a plant with a median DNA content (4.71pg) compared to the others presented intermediate yield and composition between the two previous groups. Thus a direct relationship between the DNA content and the qualitative and quantitative characteristics of the essential oils of Psidium cattleyanum was observed. In the vegetable and larvicide bioassays, the oils showed activity and demonstrated potential as bioherbicides and biolarvicides.